Composition, diversity, and dominance of woody and arborescent plants in community forests of Tawangmangu, Central Java, Indonesia - NABILA DHILA SEPTHIA; OLINDA AYU SAFITRI; RANI RACHMA ASTINING PUTRI; ROI ANDRIANTO; NUR ROHMAYANI ANGGELIKA PUTRI; DIANCAHYA MELATI DARMA SETYASIH; RIDA AYU SURYA PUTRI; YAQUT AMJAD ADILLAH RAHARJO; RINOA SALSABILA IZDIHAR; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2026)
Abstract. Septhia ND, Safitri OA, Putri RRA, Andrianto R, Putri NRA, Setyasih DMD, Adrianto R, Putri NRA, Setyasih DMD, Putri RAS, Raharjo YAA, Izdihar RS, Setyawan AD. 2026. Composition, diversity, and dominance of woody and arborescent plants in community forests of Tawangmangu, Central Java, Indonesia. Biodiversitas 27 (6): d270626. https://doi.org/10.13057/biodiv/d270626. Community forests are fine-grained production landscapes in which planting and harvesting decisions can generate marked differences in woody-plant composition over short distances. We characterized woody and arborescent plant composition, diversity, dominance, and turnover in community forests of Plumbon, Nglebak, and Sepanjang villages, Tawangmangu, Central Java, Indonesia. Field inventories were conducted in October 2024 in fifteen documented 20×20 m plots (five per village; 0.20 ha reported per village). The recoverable dataset was a species-by-village matrix comprising 934 recorded individuals assigned to 33 taxa and 18 families. From this matrix, we recalculated recorded-individual density, observed and rarefied richness, Shannon diversity, Pielou evenness, Hill diversity, Berger-Parker dominance, and pairwise compositional similarity. Sepanjang had the greatest observed richness (25 taxa), rarefied richness at 266 individuals (25.00), Shannon diversity (2.637), Pielou evenness (0.819), and Hill ¹D (13.97), the latter approximately 2.6 times the value for Nglebak (5.30). Plumbon was intermediate (23 taxa; rarefied richness 21.75; Shannon diversity 2.259), whereas Nglebak had the lowest richness (17 taxa; rarefied richness 16.60) and diversity (Shannon 1.668), with Pinus merkusii accounting for 57.7% of recorded individuals. Across villages, P. merkusii, Swietenia macrophylla, and Toona ciliata comprised 52.9% of all individuals. Eleven taxa occurred in all three villages, whereas 12 were recorded in only one village. Pairwise Jaccard similarity ranged from 0.448 to 0.548, indicating appreciable local turnover. These patterns show substantial variation in dominance and compositional breadth among nearby managed forests. Because plot selection was purposive and plot identities were not recoverable, the analysis is descriptive and does not support causal inference about elevation or management. Future studies should use permanent, voucher-supported plots with complete stem-level measurements to evaluate diversity, structure, and carbon dynamics.